Fisheries management in randomly varying environments: Comparison of constant, variable and penalized efforts policies for the Gompertz model - Brites, Nuno M. (2019)
In a previous paper, we discussed the use of an optimal variable effort fishing policy versus an optimal sustainable constant effort fishing policy in terms of the expected accumulated discounted profit during a finite time interval. We concluded that there is only a slight reduction in profit when choosing the applicable optimal sustainable constant effort fishing policy instead of the optimal variable effort fishing policy, which leads to major disadvantages in practice. In this paper, we confirm these conclusions by considering a different model, the Gompertz model, and by using another realistic dataset of parameters and a more general profit structure. We also show that some of the disadvantages of the optimal variable effort fishing policy, namely those related to social objectives, are eliminated by considering a penalized profit with an artificial running energy cost on the effort. However, the applicability problems remain. We also show that the profit advantage of this optimal penalized variable effort policy over the optimal sustainable constant effort policy is even smaller than the already very small advantage of the non-penalized policy. This further reinforces the robustness of our previous conclusions that the optimal sustainable constant effort policy, which does not have the shortcomings of the optimal variable effort fishing policy, is only slightly less profitable than it.